Natural Enemies of Honey Bees Apis Cerana F and Associated Problems in Beekeeping in Kaski, W Nepal. - Ranabhat, Nar Bahadur; Tamrakar, Ananda Shova (Journal of Natural History Museum, 2009)
A study was conducted at the southern belt of Kaski District during August 2003 to July 2004 to identify natural enemies of honey bee Apis cerana Fab. and associated problems in beekeeping. Four species of wasps viz: Vespa velutina, V. bicolor, V. tropica and V. basalis were observed preying on Apis cerana. Six species of Ants were collected from hive attacking honey bees viz Componatus sp, Sima sp, Monomorium sp, Myrmica sp and two unidentified. Four species of spider viz Palatar indicus, Ariope areuta and the other two belonging to family Theridae and Araneidae were collected from the hives. Two species of Birds, Green bee- Eater and Drongo; One species of Beetle, One Chalcid (Antrocephalus sp) were identified.The disease Thaisac brood, Mite, Wax Moth and pesticide damage, deforestation, absconding of bees, lack of technical knowledge were important problems for apiculture in study area. Key words: Apis cerana F; Enemies; Pesticide; Absconding; Kaski Journal of Natural History Museum Vol. 24, 2009 Page: 89-95